NASIONALISME H.O.S. TJOKROAMINOTO DALAM FILM GURU BANGSA HOS TJOKROAMINOTO KARYA SUTRADARA GARIN NUGROHO - Dewi Puspitasari; Retno Dewi Ambarastuti (Puitika, 2017)
HOS Tjokroaminoto is one of national heroes known as Guru Bangsa (Teacher of the Nation). Tjokroaminoto gets this title as he and his thought inspire Indonesian political figures. Tjokroaminoto is the only person in the beginning of 20th century who vocally and bluntly stated that Indies (Indonesia) had to establish its own governance. It is then termed the independence. Independence can be realized with the awareness of national consciousness in the national level, not in local level anymore.The movie entitled Guru Bangsa HOS Tjokroaminoto tells about the history reflecting one of Indonesian national figures, Tjokroaminoto. This movie tells about Tjokroaminoto as the main figure driving the nationalism and describes the history of Indonesia. The interesting aspects from this movie are the nationalism values described on Tjokroaminoto. In this research, the researcher analyze the movie entitled Guru Bangsa HOS Tjokroaminoto with historical literature approach in order to reveal the nationalism thought of Tjokroaminoto and behavior supporting his thought. This research is expected to raise the nationalism awareness in the recent young generation of Indonesia. Based on the research result, there are four main facts about the nationalism in Tjokroaminoto in the movie entitled Guru Bangsa HOS Tjokroaminoto. These historical facts are nationalism thought and behavior of Tjokroaminoto based on four factors of nationalism according to Hertz (1958), (1) Desire to achieve the unity (in 1912, Tjokroaminoto joined Sarekat Islam/Islamic Union), (2) Desire to achieve the independence (in 1905 Tjokroaminoto retired from his job as clerk), (3) Desire to achieve independence, superiority, authenticity, and distinctiveness by wearing blangkon and jarik (cloth) as the nationalism symbol and by wearing suit and bowties to show the equality with foreign nation in terms of thought, (4) Desire to catch up the honor of nation with the progressive idea of Tjokroaminoto, compulsory education for 15 years.